Staff Management in Social Security Hospitals in Tehran: Challenges and Solutions - Asra Khalili; Ali Mohammad Mosadegh Rad; SHahram Ghafary; Ebrahim Jaafaripooyan (بیمارستان)
Background and purpose: Effective management of human resources is crucial for improving healthcare services, as personnel are an organization's most valuable asset. This study aims to identify challenges in human resource management and propose solutions to enhance service quality in hospital settings. Methods: This qualitative study employed semi-structured interviews with 53 managers and key decision-makers from Social Security hospitals in Tehran, using purposive and snowball sampling techniques. Thematic analysis was utilized to analyze the data. The validity and reliability of the qualitative findings were ensured through participant and expert review methods. Results: The study identified numerous human resource challenges, categorized into five main groups and 20 subgroups. Key issues included flawed recruitment and hiring processes, unfavorable working conditions, weak human resource organization, inadequate staff training, and ambiguity in employment laws and regulations. Proposed solutions, classified into five main groups and 29 subgroups, encompassed: enhancing recruitment and hiring processes, fostering a dynamic organizational culture, improving human resource productivity and efficiency, transforming hospitals into learning organizations, providing comprehensive and effective training, and increasing transparency in rules and regulations, particularly in job descriptions. Conclusion: Regular identification of human resource management challenges and implementation of evidence-based, scientific, and operational solutions can significantly improve human resource management and, consequently, hospital performance in Social Security hospitals.